2018
DOI: 10.1007/s12671-018-1011-3
|View full text |Cite
|
Sign up to set email alerts
|

Mindfulness-Based Stress Reduction for Parents of Children with Developmental Delays: Understanding the Experiences of Latino Families

Abstract: Parents of children with developmental delays (DD) report elevated mental health difficulties compared to parents of children with typical development, which appear largely associated with child behavior problems. Latino parents of children with DD may experience heightened risk for poor mental health outcomes due additional stressors associated with minority status. Mindfulness-Based Stress Reduction (MBSR) appears to be efficacious for reducing parenting stress and improving wellbeing in families of children… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 65 publications
0
29
1
Order By: Relevance
“…When the initial search conducted in August 2018 was updated in October 2018, five additional studies were identified by the first author. Two of these, Chan and Neece (2018) and Neece et al (2018), also appeared to report data from a group of participants overlapping with those used in Neece (2014). As these two new studies and Neece (2014) all reported on parenting stress, the parenting stress outcomes from Chan and Neece (2018) and Neece et al (2018) were not included in this review.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…When the initial search conducted in August 2018 was updated in October 2018, five additional studies were identified by the first author. Two of these, Chan and Neece (2018) and Neece et al (2018), also appeared to report data from a group of participants overlapping with those used in Neece (2014). As these two new studies and Neece (2014) all reported on parenting stress, the parenting stress outcomes from Chan and Neece (2018) and Neece et al (2018) were not included in this review.…”
Section: Resultsmentioning
confidence: 96%
“…Two of these, Chan and Neece (2018) and Neece et al (2018), also appeared to report data from a group of participants overlapping with those used in Neece (2014). As these two new studies and Neece (2014) all reported on parenting stress, the parenting stress outcomes from Chan and Neece (2018) and Neece et al (2018) were not included in this review. The child outcome reported by Chan and Neece (2018) was not included in Neece (2014), so this child outcome is reported in Table 3, also under Neece (2014).…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…To our knowledge, most interventions have been conducted with predominantly Caucasian participants. Most studies with culturally diverse populations did not examine differences in outcomes based on race, ethnicity, culture, or religions, with the exception of a study by Neece et al (2019) that found that participation in MBSR with simultaneous English-Spanish interpretation resulted in improved mental health for Latino parents of children with developmental delay. Formative research is needed to explore the extent to which mindfulness and compassion practices align with the cultural or spiritual values of communities of color and inform the design of culturally relevant interventions.…”
Section: Future Directionsmentioning
confidence: 99%
“…While participants' parenting experiences may be discussed, no behavioral parenting skills are taught. A few RCTs have evidenced the outcomes of mindfulness-based programs for parents and their children, including reduced parental stress (Chaplin et al, 2018), improved parental mental health (Dykens et al, 2014; Neece et al, 2018), as well as reduced child behavioral problems (Neece et al, 2018). Nonetheless, many studies in this area lacked experimental designs in their evaluation, as the research field is still in its infancy, and it is unclear to what degree these mindfulness-based parenting programs are effective for enhancing behavioral parenting skills.…”
Section: A Third-wave Cognitive Behavioral Approach To Parenting Intementioning
confidence: 99%